2016
DOI: 10.1590/s1677-5538.ibju.2015.0646
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference between presence of single stone and multiple stones in flexible ureterorenoscopy and laser lithotripsy for renal stone burden <300mm2?

Abstract: In this study, we aim to evaluate and compare the effectiveness of flexible ureterorenoscopy (f-URS) for solitary and multiple renal stones with <300 mm2 stone burden. Patients' charts who treated with f-URS for kidney stone between January 2010 and June 2015 were reviewed, retrospectively. Patients with solitary kidney stones (n:111) were enrolled in group 1. We selected 111 patients with multiple kidney stones to serve as the control group and the patients were matched at a 1:1 ratio with respect to the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
2
12
0
1
Order By: Relevance
“…RIRS is used in the treatment of multiple kidney stones. Success is lower than the single stones of the same size (7). In our study, we aimed to report our RIRS experience in the treatment of multi-caliceal and multiple kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…RIRS is used in the treatment of multiple kidney stones. Success is lower than the single stones of the same size (7). In our study, we aimed to report our RIRS experience in the treatment of multi-caliceal and multiple kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Ozgor et al 13 reported that RIRS technique resulted in lower stone-free rates in patients with multiple renal stones when (located in minimum two calyces) was reported to be 53.9% in a recent study 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that although multicalyceal stones were operated in our study, only one access was used for PNL. However, based on previously reported high complication rates in PNL operations performed with multiple access 13,28 , we prefer single access in our department.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations